3D Seismic Anatomy of a Watershed Reveals Climate‐Topography Coupling That Drives Water Flowpaths and Bedrock Weathering. Issue 12 (10th December 2021) - Wang, Wei; Nyblade, Andrew; Mount, Greg; Moon, Seulgi; Chen, Po; Accardo, Natalie; Gu, Xin; Forsythe, Brandon; Brantley, Susan L.
Abstract: To investigate how bedrock transforms to soil, we mapped the topography of the interface demarcating onset of weathering under an east‐west trending shale watershed in the Valley and Ridge province in the USA Using wave equation travel‐time tomography from a seismic array of >4, 000 geophones, we obtained a 3D P‐wave velocity (Vp) model that resolves structures ∼20 m below land surface (mbls). The depth of mobile soil and the onset of dissolution of chlorite roughly match Vp = 600 m/s and Vp = 2, 700 m/s, respectively. Chlorite dissolution initiates porosity growth in the shale matrix. Depth to the 2, 700 m/s contour is greater under the N‐ as compared to S‐facing hillslopes and under sub‐planar as compared to concave‐up land surfaces. Broadly, the geometries of the 'soil' and 'chlorite' Vp contours are consistent with the calculated potential for shear fracture opening under weak regional compression. However, this calculated fracture potential does not consistently explain observations related to N‐ versus S‐facing aspect nor fracture density observed by borehole televiewer. Apparently, regional compression is only a secondary influence on Vp: the primary driver of P‐wave slowing in the upper layers of this catchment is topographic control of reactive water flowpaths and their integrated effects on weathering. The Vp result is best explained as the long‐term integrated effect of groundwater flow‐induced geochemical weathering of shale in response to climate‐driven patterns of micro‐ and macro‐topography. Plain Language Summary: Our capacity to understand the subsurface structure that controls storage and flow of groundwater relies largely on point measurements at boreholes and outcrops. In this study, we developed understanding of the subsurface structure beneath a shale watershed in three‐dimensions (3D) by using a dense seismic array of >4, 000 geophones. We obtained a 3D P‐wave velocity model with resolution to image ∼20 m below the land surface. By correlating our velocity structures to borehole logs and geochemical measurements at the same site, we were able to explore the "landscape" defined by the bottom of the mobile soil and the onset of porosity growth by clay weathering. This 3D image shows how the depth of soil and onset of dissolution varies with orientation with respect to the sun (aspect) and as a function of planar versus concave‐up land surfaces (curvature). Some of the subsurface structure can be explained by opening of cracks in upper layers in response to a weak compressional regime. However, the structure is best explained by the effect of bedrock weathering that was primarily driven by climate and topographic control of reactive water flow, with regional compression playing a secondary role. Key Points: To understand the structure beneath the land surface, we constructed a three‐dimensional P‐wave velocity model of a shale watershed The spatially varying depth of mobile soil and the onset of dissolution of chlorite were mapped based on Vp of 600 and 2, 700 m/s The subsurface structure represents the long‐term integrated effect of water‐induced weathering responding to both climate and topography